Exploring tourists intention to stay at green hotel: The influences of environmental attitudes and hotel attributes - Mohd Noor, Nor Azila; Hasan, Hasnizam; Kumar M., Dileep (Macrotheme Capital Management, 2014)
The hospitality industry as a whole is being pressures by many forces to become more environmentally friendly.Hotels are becoming more aware of their impact and are taking initiatives and participating in green initiatives. As more tourists are becoming increasingly concerned regarding the environment and environmentally products, it is crucial for the hotel industry to explore this concept of green hotels in more detail.In the hotel industry, green hotels are defined as lodging establishments that have made a commitment to diverse ecologically sound practices such as saving water, energy, and reducing solid waste. This study examines the influence of environmental attitudes and hotel attributes on tourists’ intention to choose green hotels as their preferred accommodation. By using intercept survey method, data were collected from tourists at the international airport in Malaysia. Present study confirms previous findings on the relationship between attitudes towards the environment and environmental-friendly behavior, that is, tourists with high environmental attitudes are more willing to stay at green hotel.The present study found a positive and significant relationship of green hotel attributes and intention to stay at green hotel among tourists. This implies that tourists who have greater interest with green hotels are more likely to identify which hotels that conduct a higher degree of green practices. The theoretical implications and managerial implications of these findings are discussed.